Transcriptome Analysis Reveals Differences in Anthocyanin Accumulation in Cotton (Gossypium hirsutum L.) Induced by Red and Blue Light - Shao, Dongnan; Zhu, Qian-hao; Liang, Qian; Wang, Xuefeng; Li, Yanjun; Sun, Yuqiang; Zhang, Xinyu; Liu, Feng; Xue, Fei; Sun, Jie (Frontiers in Plant Science, 2022)
Many factors, including illumination, affect anthocyanin biosynthesis and accumulation in plants. light quality is the key factor affecting the process of photoinduced anthocyanin biosynthesis and accumulation. We observed that the red color of the Upland cotton accession Huiyuan with the R1 mutation turned to normal green color under light-emitting diodes (LEDs), which inspired us to investigate the effect of red and blue lights on the biosynthesis and accumulation of anthocyanins. We found that both red and blue lights elevated accumulation of anthocyanins. Comparative transcriptomic analyses, including Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and GSEA, revealed that genes differentially expressed under different light conditions were enriched with the pathways of circadian rhythm, phenylpropanoid biosynthesis, anthocyanin biosynthesis, and flavone and flavonol biosynthesis. Not surprisingly, all the major structural genes related to biosynthesis of anthocyanins, including the key regulatory MYB transcription factor (GhPAP1D) and anthocyanin transporter (GhGSTF12), were induced by red or blue light treatment. However, LARs and MATEs related to biosynthesis of proanthocyanidins were more significantly up-regulated by red light radiation than by blue light radiation. Vice versa, the accumulation of anthocyanins under red light was not as high as that under blue light. In addition, we demonstrated a potential role of GhHY5, a key regulator in plant circadian rhythms, in regulation of anthocyanin accumulation, which could be achieved via interaction with GhPAP1D. Together, these results indicate different effect of red and blue lights on biosynthesis and accumulation of anthocyanins and a potential module including GhHY5 and GhPAP1D in regulation of anthocyanin accumulation in cotton. These results also suggest that the substrates responsible the synthesis of anthocyanins under blue light is diverted to biosynthesis of proanthocyanidin under red light.